Building Expert Medical Prognostic Systems Using Voronoi Diagram. (17th February 2015) - Ivanchuk, Maria A.; Malyk, Igor V.
Abstract : The method of building expert systems for medical prediction of severity in patients is purposed. The method is based on using Voronoi diagrams. Examples of using the method are described in the paper.